Endoscopic Evidence of Peptic Ulcer Complicated with Gastrointestinal Bleeding in Children - S.O. Sokolnyk (Zaslavsky O.Yu., 2015)
The paper presents a comparative analysis of endoscopic picture of peptic ulcer, non-complicated and complicated with gastrointestinal bleeding, in children. It is found that in the vast majority of patients with gastrointestinal bleeding of ulcer origin, single larger ulcers with predominant localization on the posterior wall of the duodenal bulb, helicobacter-associated, accompanied by moderate hyperacidity, are being detected.